An X-ray diffraction study of corrosion products from low carbon steel (2003)
ABSTRACT: It was found in earlier work a decrease in the corrosion rate from low carbon steel when it was subjected to the action of a combined pollutant concentration (S04^~ = 10"^ M + Cl" = 1.5 X 10~^ M). It was also found that large magnetite content of the rust was related to higher corrosion rates. In the present study corrosion products are further analyzed by means of X-ray diffraction to account for composition changes during the corrosion process. It is found that lepidocrocite and goethite are the dominant components for the short-term corrosion in all batches considered while for log-term corrosion lepidocrite and goethite dominates if the corrosion rate is low and magnetite dominates if the corrosion rate is high. The mechanism for decreasing the corrosion rate is related to the inhibition of magnetite production at this particular concentration.